Asymptotic properties of the algebraic moment range process - Holger Dette; Fabrice Gamboa (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2005)
Moment spaces, weak convergence, large deviations, canonical moments, range of the moment space, beta-distribution
Keywords: 519; Moment spaces; weak convergence; large deviations; canonical moments; range of the moment space; beta-distribution